The Analysis Pack for Economics of Land Degradation (APELD) - Yigezu, Yigezu (International Center for Agricultural Research in the Dry Areas, 2024)
The Analysis Pack for Economics of Land Degradation (APELD) is an innovation that involves three separate but complementary modules each with specific function. The first module enables researchers and experts to estimate the quantities and monetary values of ecosystem services (ESS) lost due to inaction, i.e., due to no or insufficient efforts to combat land degradation (LD). Assuming that a package of suitable policy, institutional, and technological innovations for combating LD have been identified, the second module enables to estimate the benefits of action (i.e., the benefits of implementing the innovation package) in terms of the quantities and monetary values of ESS that can be prevented from being lost or new ESS that can be generated due to the interventions. The third and last module estimates the cost of implementing the package of innovations over a given planning horizon (or planning period preferably of 10-20 years), the total discounted benefits of action over the entire planning period, and ultimately provides estimates of the returns on investment that are provided in the form of benefit:cost ratios – i.e., the monetary values of the returns on every dollar invested in combating LD. All three modules provide the disaggregated estimates for each province x biome x LD class combination as well as aggregates at LD class, biome, province, and national levels. The costs and benefits are also disaggregated by ESS classifications (i.e., use, and non-use values and the use values are further disaggregated into direct and indirect use values)